Photo-Fenton reaction derived self-cleaning nanofiltration membrane with MOFs coordinated biopolymers for efficient dye/salt separation - Li, Jian (2023)
Membrane technology has been widely used in textile industry for the separation of dye/salt mixtures. However, membranes inevitably suffered from the fouling issue, which greatly abated the water permeability and reduced the separation efficiency of membranes. Herein, a novel thin film nanocomposite (TFN) nanofiltration (NF) membrane was prepared by introducing photocatalytic sensitive material into the selective layer to directly degrade the foulants on the membrane surface. This functional selective layer was achieved by a complexation of carboxymethyl cellulose (CMC) and MIL-53 (Fe), which greatly enhanced the self-cleaning ability of the TFN membrane while MIL-53 (Fe) was served as nanofiller and photocatalyst simultaneously. The optimized TFN NF membrane modified with 0.5 mg CMC and 0.075 mg MIL-53 (Fe) exhibited a high pure water permeability of 39.83 L m−2 h−1 bar−1, while maintaining high dye rejections above 99.00 % for CR, G250 and MB. Meanwhile, the obtained membrane exhibited impressive rejections of salts (61.49 % for Na2SO4 and 17.22 % for NaCl). This simple fabrication strategy provided new insights to augment the separation performance of TFN NF membrane with self-cleaning ability in organic separation systems.